2020
DOI: 10.3389/fphys.2020.590180
|View full text |Cite
|
Sign up to set email alerts
|

TFII-I/Gtf2i and Erythro-Megakaryopoiesis

Abstract: TFII-I is a ubiquitously expressed transcription factor that positively or negatively regulates gene expression. TFII-I has been implicated in neuronal and immunologic diseases as well as in thymic epithelial cancer. Williams-Beuren Syndrome (WBS) is caused by a large hemizygous deletion on chromosome 7q11.23 which encompasses 26-28 genes, including GTF2I, the human gene encoding TFII-I. A subset of WBS patients has recently been shown to present with macrocytosis, a mild anemia characterized by enlarged eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…TFII-I as a ubiquitously expressed transcription factor can regulate gene expression negatively. 63 In addition, research has shown that the high methylation of recognition gene can affect transcription factor TFII-I binding to the region. 64 Thus, we can speculate that in patients with HTR1B rs6298 allele AA/AG and high HTR1B-3-61, expression of HTR1B receptors is higher, making early antidepressant treatment more effective.…”
Section: Discussionmentioning
confidence: 99%
“…TFII-I as a ubiquitously expressed transcription factor can regulate gene expression negatively. 63 In addition, research has shown that the high methylation of recognition gene can affect transcription factor TFII-I binding to the region. 64 Thus, we can speculate that in patients with HTR1B rs6298 allele AA/AG and high HTR1B-3-61, expression of HTR1B receptors is higher, making early antidepressant treatment more effective.…”
Section: Discussionmentioning
confidence: 99%
“…5A). Known regulators of hematopoiesis, including Salmonella pathogenicity island 1 (SPI1/PU.1), a key player of myeloid and lymphoid development (31)(32)(33)(34)(35); general transcription factor IIi (GTF2I), recently identified to have a function in erythro/ megakaryopoiesis (36); and the histone deacetylase 3 (HDAC3), which has been shown to regulate the activity of MPPs (37), were also altered in Nup358 −/− MPP2 clusters. Considering that these factors shuttle between the nucleus and the cytoplasm and Nup358 main function in regulating the nuclear import of specific proteins (38), we investigated whether Nup358 ablation affected their nuclear translocation.…”
Section: Nup358 Regulates the Function And Nuclear Translocation Of H...mentioning
confidence: 99%